Barriers and facilitators to early mobilisation in Intensive Care: A qualitative study. Issue 4 (November 2015) - Barber, Elizabeth A.; Everard, Tori; Holland, Anne E.; Tipping, Claire; Bradley, Scott J.; Hodgson, Carol L.
Abstract: Objectives: To determine the barriers and facilitators of early mobilisation in the Intensive Care Unit. Background: It is well established that mobilising critically ill patients has many benefits, however it is not occurring as frequently as expected. The causes and ways to change this are not clearly understood. Methods: A qualitative descriptive study involving focus groups with medical, nursing and physiotherapy clinicians, from an Australian quaternary hospital Intensive Care Unit. Results: The major themes related to barriers included the culture of the Intensive Care Unit; communication; and a lack of resources. Major themes associated with facilitating early mobilisation included organisational change; improved communication between medical units; and improved resources. Conclusions: Early mobilisation was considered an important aspect of critically ill patient's care by all clinicians. Several major barriers to mobilisation were identified, which included unit culture, lack of resources, prioritisation and leadership. A dedicated mobility team led by physiotherapists in the ICU setting could be a viable option to address the identified barriers related to mobility.